Sistema de RPG para o ensino de física - Macêna Júnior, André Gonçalves (2018)
The present work brings an educational product that uses RPG (Role-Playing Game) as a tool for the teaching of the discipline of Physics in High School. The use of RPG in the classroom aims to arouse the interest of the student in the discipline of Physics while trying to bring meaning to the contents seen in the classroom through the resolution of problem situations that must be solved with their previous knowledge. This work also provides a general explanation of what RPG is, in addition to relating previous works that link RPG and teaching, besides showing the application and analysis, through the Discursive Textual Analysis method and the impressions of the teacher, RPG adventure applied in a mixed class of 1st and 2nd grade high school students from a private school in Maceió in the state of Alagoas. Through the analysis of the collected materials and the observations made during and after the application, it is noticed a greater interest of the students by the discipline of Physics, besides improvements in the argumentation and exposition of ideas.